P126The role of MIP1 in cardiac myocyte hypertrophy and survival. (15th July 2014) - Mansfield, C; Buyandelger, B; Kostin, S; Knoell, G; Toliat, MR; Perrot, A; Haverkamp, W; Milting, H; Nurnberg, P; Knoell, R
Abstract: Purpose: Mutations in several sarcomeric Z-disc proteins, such as muscle LIM protein (MLP), have been shown to cause hypertrophic and dilated cardiomyopathies. The transcription factor MIP1 has been identified as a novel MLP interacting protein which is important in the cardiac stress response and able to cause cardiac hypertrophy in vivo. Here we examine, in vitro, the mechanisms behind this cardiac phenotype and investigate potential disease causing mutations in this protein. Methods and Results: Adenoviral overexpression of MIP1 in adult and neonatal rat cardiomyocytes (NRCMs) showed that MIP1 induces cardiac myocyte hypertrophy, as seen by increased cell size and real-time impedance measurements (n=10, p<0.01). MIP1-induced hypertrophy was significantly reduced by calcineurin inhibition by cyclosporine A (0.2μM; n=4, p<0.05). We also analyzed apoptotic events and impedance measurements after doxorubicin (1μM) treatment and found that MIP1 overexpression protects from apoptosis (n=7, p<0.05). A recent large Genome-wide Association Study suggested a role for genetic variation of MIP1 in disease susceptibility. We sequenced the human MIP1 gene in 916 unrelated individuals affected by cardiomyopathy and heart failure and identified three novel heterozygous variants (G179S, A188V, Q531R) and one that had been described previously (T106M). Adenoviral expression of all four mutants resulted in hypertrophy of NRCMs (n=5, p<0.01) and the mutant proteins were shown to be mislocalised in a proportion of adult cardiac myocytes (G179S 14.6%, A188V 22.6%, Q531R 25.7%) or not stably expressed (T106M). Hypertrophy induced by mutant MIP1 expression was not affected by calcineurin inhibition, indicating a different mechanism, and mutant MIP1 is not as efficient as the wild-type protein at protecting against doxorubicin-induced apoptosis (n=5, WT vs. -T106M p<0.05, -G179S p<0.05, -A188V p<0.01, -Q531R p<0.05). Conclusions: MIP1 regulates cardiac hypertrophy and cell survival, a recognized dual-property of genes of central importance for cardiac myocyte biology. The effects of MIP1 are dependent on calcineurin and mutations in MIP1 may be a potential cause of hypertrophic cardiomyopathy and heart failure.